Sistem Informasi Administrasi Pemerintahan Desa pada Desa Cilayung Kabupaten Kuningan (Jurnal Teknologi dan Informasi, 2020)
Good and appropriate government public services can be seen from the clarity and accuracy of service procedures, requirements, and timetables for completion. In improving the quality of public services, the government seeks to utilize technology by implementing e-government following Presidential Instruction of the Republic of Indonesia No. 3 of 2003. E-government hasn't yet been applied to Cilayung Village, Ciwaru District, Kuningan Regency, so residents still do not know information about public service procedures, there are still duplication of population data, a long time to settle in making certificates, there is a duplication of numbers reference certificate, and incompatibility of inventory data with existing inventory in the village. The purpose of this research is to overcome the problems of Cilayung Village governance in the process of population registration, making certificates and village inventory using information systems. This research uses a system approach method, OOAD, system design tools using UML and system development methods using the Prototype method. The results of this research are the village administration information system makes it easy for residents to obtain information on procedures and requirements for public services, provide information on the status of completion of certificates, there is no duplication of population data and reference numbers for certificates, and the corresponding village inventory data.